Analisis unjuk kerja motor bensin 4 langkah 1 silinder 100 cc berbahan bakar etanol - I Made Mara; I Made Adi Sayoga; I Made Nuarsa; Ida Bagus Alit; Kade Wiratama (Universitas Mataram, 2020)
In line the population growth, technological developments and the increasing of vehicles, the necessary of fuel is increase. Therefore, the people try to find an alternative fuel that is ethanol as vehicle fuel. To increase the performance and efficiency to use of ethanol fuel in an engine is by varying the ignition timing.This research aimed to investigate the influence of ignition timing to torque, power and specific fuel consumption effective (SFCe) with 96% ethanol fuel. in an engine four stroke single cylinder 100 cc Honda Astrea Legenda. The ignition timing variation are 15˚, 20˚ and 25˚ before TDC and the engine speed are 1500, 2500, 3500, 4500, and 6000 rpm.The results show that the engine has better performance when the engine running on the ignition timing is advanced. The highest torque at 20˚ ignition time before TDC 0.868 kgf.m at 6000 rpm, the highest effective power at 20˚ ignition time before TDC of 7.272 ps at 6000 rpm, and the lowest SFCe at 20˚ ignition time before TDC is 0, 08 kg / PS.hour at 6000 rpm.